How Is Gross Profit Margin Overestimated in China? - Fulei Shi; Bingbing Huang; Chuanqi Wu; Liang Jin (Journal of Mathematics)
At present, the index of gross profit margin is overestimated in China. However, this problem has not attracted enough attention. This paper explores the theoretical limitations of the current revenue that lead to the overestimation of the gross profit margin. Then, we present the concept of revenue to correct the limitations of the current revenue. Moreover, we test the impact on the information content of gross profit margin under revenue caliber. The findings are as follows: (1) The current revenue includes some unrealized items such as in-price tax, so it is not completely consistent with the definition of revenue from the perspective of accounting, which will lead to the overestimation of gross profit margin. Therefore, the current revenue should exclude the in-price tax, bad debt loss, and cash discount in order to obtain the revenue. The gross profit margin based on the revenue can reflect the profitability of the company’s basic business more objectively. (2) The empirical test shows that the gross profit margin based on the revenue has higher information content compared with the gross profit margin based on the current revenue. (3) The current gross profit margin is overestimated by 1.36 percentage points because of the limitations of the current revenue.